A Software Reliability Model Using Quantile Function. (11th March 2014) - Thomas, Bijamma; Nellikkattu, Midhu Narayanan; Godan Paduthol, Sankaran
Abstract : We study a class of software reliability models using quantile function. Various distributional properties of the class of distributions are studied. We also discuss the reliability characteristics of the class of distributions. Inference procedures on parameters of the model based on L-moments are studied. We apply the proposed model to a real data set.